Réponses

  • Utilisateur Brainly
2014-05-04T09:54:37+02:00
Bonjour, 

Résoudre les équations :

A- 
(x - 3) = - 7 (3 - 3x)
x - 3 = - 21 + 21x
- 3 + 21 = 21x -x
18 = 20x
18/20 = x
x = 9/10

B- 
2(x + 4) - 3x = 5(x - 3)
2x + 8 - 3x = 5x - 15
8 + 15 = 5x + 3x - 2x
23 = 6x
x = 23/6

C-
- 12(2 - x) = - 24
- 24 + x = - 24
x = - 24 + 24
x = 0

Bonne journée à toi! =)
Meilleure réponse !
2014-05-04T09:54:37+02:00
A.('x-3)=-7(3-3x)
a  x-3 =  -21 +21x
 x +21x = -21 +3
22x = -18
x = -18/22
x = -9 /11

b.2(x+4)-3x=5(x-3)
2x +8 -3x = 5x -15
-x -5x = -15 -8
-6x = -23
x = -23/-6
x = 23/6

c.-12(2-x)=-24
-24 +12x = -24
12x = -24 +24
12x =0
x = 0